Evaluation of information system success in particular organization - Boateng, Asare (Univerzita Pardubice, 2018)
The aim of the thesis is to provide a thorough overview of the factors that influence Information System implementation success and to verify whether these factors are critical to the success in a real company. The study identifies key factors of IS implementation success through a systematic literature review of papers published between the years 2000 2016 on CSFs. The research study follows the process of categorizing the CSFs under four domains (Social System, Technical System, Project Specifics and External Factors). The results of the findings will help verify whether it be used in a practical case.
Hodnocení úspěšnosti informačního systému v konkrétní organizaci
Keywords: informační systém (IS); plánování podnikových zdrojů (ERP); kritické faktory úspěchu (CSFs); information system (IS); enterprise resource planning (ERP); critical success factors (CSFs)